Analysis of Worker Compliance Level in the Use of Personal Protective Equipment (PPE) in The Work Area - Pahlevi, Fiqo; Anggara, Arie; Imron , I. (Golden Ratio of Data in Summary, 2026)
This study aims to analyze the level of worker compliance in the use of PPE at PT Ombilin Fusi Nusantara and examine the relationship between age, education level, length of service, knowledge, and attitude towards such compliance. This study uses a descriptive quantitative approach with a cross-sectional method. Data were collected through questionnaires and direct observation of 100 field worker respondents. Data analysis was carried out univariately and bivariately using the Chi-Square test. The results showed that 57% of workers were compliant in using PPE, while 43% were still not compliant. There was a significant relationship between the variables of age, education level, length of service, knowledge, and attitude with the level of compliance in the use of PPE (p < 0.05). Attitude and knowledge factors were the dominant aspects that influenced compliance. This study concludes that although most workers have complied with the use of PPE, increased education and supervision are still needed to achieve optimal compliance. It is hoped that the results of this study can be a reference in efforts to improve the implementation of OHS in companies.